Uranium mineralogy, geochemistry, and the environment - Burns, Peter C.; Finch, Robert (Robert James) (Reviews in mineralogy ;, 2018)
Volume 38 of Reviews in Mineralogy provides detailed reviews of various aspects of the mineralogy and geochemistry of uranium. We have attempted to produce a volume that incorporates most important aspects of uranium in natural systems, while providing some insight into important applications of uranium mineralogy and geochemistry to environmental problems. The result is a blend of perspectives and themes: historical (Chapter 1), crystal structures (Chapter 2), systematic mineralogy and paragenesis (Chapters 3 and 7), the genesis of uranium ore deposits (Chapters 4 and 6), the geochemical behavior of uranium and other actinides in natural fluids (Chapter 5), environmental aspects of uranium such as microbial effects, groundwater contamination and disposal of nuclear waste (Chapters 8, 9 and 10), and various analytical techniques applied to uranium-bearing phases (Chapters 11-14).This volume was written in preparation for a short course by the same title, sponsored by the Mineralogical Society of America, October 22 and 23, 1999 in Golden, Colorado, prior to MSA's joint annual meeting with the Geological Society of America.